Proposition of a Process Method for Compactly Folding the Cross Section of Square Steel Pipes during Laterally Impact Crushing - Terada, Kosuke (Transaction of the Japan Society for Simulation Technology, 2024)
As a cross section of square steel pipe is laterally crushed, the upper/lower plates deform inward and the side plates deform outward from the original shape. When the proposed process method is applied, the upper/lower plates remain flat while the side plates are folded inward. This deformation pattern does not damage the surroundings, and makes it possible to improve impact energy absorption performance by folding the side plates in an overlapping manner. Moreover, common steel pipe structures include pipe intersections and sections where it is necessary to avoid interference with other parts such as piping, wiring, or fork claws. In such cases, the current method is to create an opening by cutting off. As a result, the structural strength will decrease, often requiring that reinforcing materials be installed as a countermeasure. However, if the opening is processed by using the proposed process method in this paper, the crushed part will remain, without a decrease in structural strength or the addition of reinforcing material. This paper discusses the results of experimental and FEM (Finite Element Method) analysis of process conditions for inward deforming side plates of square steel pipes and evaluates the impact energy absorption performance during lateral crushing.